2020
DOI: 10.1007/s00125-019-05061-y
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic and scalable strategy using mobile technology to promote sustained lifestyle changes to prevent type 2 diabetes in India and the UK: a randomised controlled trial

Abstract: Aims/hypothesis This randomised controlled trial was performed in India and the UK in people with prediabetes to study whether mobile phone short message service (SMS) text messages can be used to motivate and educate people to follow lifestyle modifications, to prevent type 2 diabetes. Methods The study was performed in people with prediabetes (n = 2062; control: n = 1031; intervention: n = 1031) defined by HbA 1c ≥42 and ≤47 mmol/mol (≥6.0% and ≤6.4%). Participants were recruited from public and private sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 32 publications
1
95
0
Order By: Relevance
“…These two things illustrate that there is an effective use of technology, but there is a shortage of human resources as technology users which is a limitation of technology use, namely the time owned by health workers in the form of working hours and a fairly high work load. This is in line with the results of research by Nanditha et al (2020) which states that electronic delivery of lifestyle and motivation advice may be less effective than if it is complemented by direct remote counseling or counseling. Long distance counseling is also hampered by the timing between the counselor and the recipient of the counseling itself.…”
Section: Discussionsupporting
confidence: 87%
“…These two things illustrate that there is an effective use of technology, but there is a shortage of human resources as technology users which is a limitation of technology use, namely the time owned by health workers in the form of working hours and a fairly high work load. This is in line with the results of research by Nanditha et al (2020) which states that electronic delivery of lifestyle and motivation advice may be less effective than if it is complemented by direct remote counseling or counseling. Long distance counseling is also hampered by the timing between the counselor and the recipient of the counseling itself.…”
Section: Discussionsupporting
confidence: 87%
“…An important difference between our study and previous RCTs [ 11 ] is that we showed that it is feasible to use a wearable technology that continually records levels of PA (ie, step count). Furthermore, our study included male and female participants compared with another study that included only male participants [ 31 ].…”
Section: Discussionmentioning
confidence: 83%
“…These are increasingly available from commercial providers at a low cost to the patient or health commissioners, but the evidence of their effectiveness in reducing the risk of type 2 diabetes is limited [ 9 , 10 ]. For example, in a recent RCT of 2062 people in India and the United Kingdom with impaired glucose tolerance, those who received 2 to 3 weekly SMS texts providing lifestyle advice did not have a significant reduction in diabetes conversion (defined by international criteria for fasting plasma glucose or hemoglobin [HbA 1c ] levels) compared with controls who received standard lifestyle advice at baseline only [ 11 ]. Similarly, a pilot pre-post noncontrolled study of a 16-week web-based DPP was associated with reduced weight and lower HbA 1c levels, improvements that persisted at the 2-year follow-up [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also note that the intensive interventions using peer-support or digital strategies for lifestyle modification have not shown evidence for diabetes prevention in South Asians. 21,22 Our experiment will thus add to the spectrum of approaches to delivery, and aims to deliver an optimal combination of resource utilisation and clinical effectiveness. We will not be able to collect individual level health expenditure data, which will limit the accuracy of our health economic evaluation.…”
Section: Discussionmentioning
confidence: 99%